The new alliance : - Dimancescu, Dan (Ballinger Pub. Co., 1986)
This book important beyond its skillful understanding of the alliances themselves, this work probes the underlying forces and the changing nature of business in a world where knowlegge, as an asset, has surged in importance relative to the more traditional view of fiscal or physical assets.